Biopolitical media : catastrophe, immunity and bare life - Meek, Allen, 1961- (New York, NY : Routledge, 2016)
'This book presents a historical account of media and catastrophe that engages with theories of biopolitics in the work of Michel Foucault, Giorgio Agamben, Michael Hardt, Antonio Negri and others. It explains how response to catastrophe in media and cultural criticism over the past 150 years are embedded in biological conceptions of life and death, contamination and immunity, race and species. Mediated catastrophe is often understood today in terms of collective memory and according to therapeutic or redemptive accounts of trauma. In contrast to these approaches this book empahsizes the use of media to record, archive and analyze physical appearance and movement; to capture viewer attention through shock; to monitor and control bodies in economies of production and consumption; to enmesh social relations in information networks; and situate subjects in discourses of victimhood, immunity, survival and resilience. Chapters are focused on historical case studies of early photography, Nazi propaganda, colonial stereotypes, Hiroshima, the Holocaust, the Cold War and the war on terror'--First preliminary page.
Includes bibliographical references and index.
Keywords: Psychic trauma and mass media; Mass media -- Psychological aspects; Biopolitics